PENERAPAN MODEL INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SOSIOLOGI MATERI STRUKTUR SOSIAL PADA SISWA KELAS XI IPS-1 DI SMAN 1 KUSAN HILIR TAHUN PELAJARAN 2014 / 2015 - Nani Whuri Widarti (Universitas Lambung Mangkurat, 2015)
Observations conducted by researchers at SMAN 1 Kusan Hilir showed (1) the lack of understanding of students of the teaching materials, (2) the students' responses to the explanation or information submitted by teachers during learning activities are very low, (3) students do not have motivation and excitement during the learning activities Sociology in the classroom, (4) low value results were obtained by the students, and (5 ) the students were not able to develop critical thinking skills in terms of understanding the problems and solving problems in the learning process. The purpose of this study was to study the process and results of the application of the inquiry model of learning Sociology whether it can increase the activity of learning, thinking and learning outcomes of students of class XI IPS-1 SMAN 1 Kusan Hilir. This study used a descriptive qualitative research with the implementation of social inquiry model on the subject. This study was conducted for 3 months from May to July 2015. The subjects were 40 students of class XI IPS-1 SMAN 1 Kusan Hilir, consisting of 18 male students and 22 female students. The results showed that the implementation of the social inquiry model to study Sociology, increased from 71,92% to 87.15%, with an average of completeness KKM reaching 78.0% to 100%, This assessment became successful if 85% of students completed with the class average of 74.Key words: Inquiry Model, Sociology, Learning Outcomes